Clinical Characteristics, Management, and Short-Term Outcome of Neonates Born to Mothers with COVID-19 in a Tertiary Care Hospital in India. (11th June 2021) - Malik, Sushma; Surve, Suchitra; Wade, Poonam; Kondekar, Santosh; Sawant, Vishal; Shaikh, Murtuja; Kuppusamy, Periyasamy; Bharmal, Ramesh; Mahale, Smita D; Modi, Deepak N; Gajbhiye, Rahul K
Lay Summary: The current pandemic of COVID-19 has affected all the countries globally. However, the adverse impact of the pandemic is more seen in the low-income and middle-income countries (LMICs). Although there is evidence on the adverse impact of the SARS-CoV-2 on the health of mothers and neonates, the evidence is mainly from high-income countries. For reducing the mortality and morbidity due to COVID-19 in LMICs, there is a need to generate evidence from the LMICs. The present study is a part of the National Registry of pregnant women with COVID-19 in India (PregCovid registry). Our study demonstrates a higher risk of adverse outcomes such as neonatal sepsis and death in the SARS-CoV-2 infected as compared to the noninfected neonates. The study also showed the risk of SARS-CoV-2 infection in 6.3% of neonates born to mothers with COVID-19. Abstract: Introduction: We describe the clinical characteristics, management, and short-term outcomes of SARS-CoV-2 neonates born to mothers with COVID-19 in a tertiary care hospital in Mumbai, India. Methods: The study is a retrospective analysis of 524 neonates born to mothers with COVID-19 admitted from 14th April 2020 to 31st July 2020. Results: SARS-CoV-2 infection was detected in 6.3% of the newborns of the mothers with COVID-19. No significant differences were observed between maturity at gestation, birth weight and sex of SARS-CoV-2 infected and noninfected newborns. The risk of sepsis was 4.09 [95% confidence interval (95% CI) 1.28–13.00] fold higher in the neonates with SARS-CoV-2 as compared to the noninfected group ( p  = 0.031). Poor feeding was significantly more common among SARS-CoV-2 infected neonates (12.1%) as compared to the noninfected neonates (2.7%) ( p  = 0.017). There was a total of 13 neonatal deaths, of which 3 deaths occurred in SARS-CoV-2 infected neonates (9%) while 10 (2.04%) in the SAR-CoV-2 negative group. The risk of neonatal death was higher in SARS-CoV-2 infected newborns [odds ratio (OR) 4.8; 95% CI 1.25–18.36]. Conclusion: Neonatal SARS-CoV-2 infection is observed in almost 6% of neonates born to mothers with perinatal COVID-19. There is a higher risk of adverse outcomes such as neonatal sepsis and death in the SARS-CoV-2 infected as compared to the noninfected neonates.